2020
DOI: 10.3390/f11010063
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Pigments in Siberian Pine and Fir under Climate Warming and Shift of the Timberline

Abstract: Research Highlights: For the first time, the Pinus sibirica Du Tour and Abies sibirica L. conifer forest at the West Sayan ridge timberline has been explored to reveal which species is likely to react to climate change and a shift of the timberline. Such a shift may modify the ecological functions of the forests. Background and Objectives: Long-term climate change has become obvious in the mountains of southern Siberia. Specifically, a half-century rise in annual mean temperatures has been observed, while prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…They found that, at the treeline, Pinus canariensis displays a drought avoidance strategy due to a great plasticity in gas exchange, antioxidants, and pigments. Pakharkova et al [18] demonstrated that Pinus sibirica Du Tour and Abies sibirica L. showed different patterns of photosynthetic pigments along an elevational gradient in the West Sayan ridge, Siberia. As the decline in photosynthetic pigments with increasing elevation was more pronounced in Pinus sibirica needles than in Abies sibirica needles, the authors conclude that under conditions of future climate warming, Pinus sibirica trees will have an advantage in colonizing zones above the present treeline.…”
mentioning
confidence: 99%
“…They found that, at the treeline, Pinus canariensis displays a drought avoidance strategy due to a great plasticity in gas exchange, antioxidants, and pigments. Pakharkova et al [18] demonstrated that Pinus sibirica Du Tour and Abies sibirica L. showed different patterns of photosynthetic pigments along an elevational gradient in the West Sayan ridge, Siberia. As the decline in photosynthetic pigments with increasing elevation was more pronounced in Pinus sibirica needles than in Abies sibirica needles, the authors conclude that under conditions of future climate warming, Pinus sibirica trees will have an advantage in colonizing zones above the present treeline.…”
mentioning
confidence: 99%
“…At the beginning of the growing season, the critical conditions of treeline habitats are a combination of negative soil temperatures, low positive air temperatures, and high illumination, aggravated by the reflection of light from spots of the snow cover. All this leads to burns and drying out of needles, which are especially pronounced in fir and prevent the advancement of its seedlings above the treeline [ 13 ]. Siberian pine partially compensates for these factors by increasing the content of carotenoids in needles and by later resumption of photosynthetic activity [ 12 ], which allows Siberian pine seedlings to occupy habitats above the forest boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling and measurements were performed in mid-April 2020, which was the end of the growing season in the area. Thus, the methods slightly differed from those applied in a previous study [ 13 ], in which sampling was done at the very beginning of the growing season.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations